(Invited) Intrinsically-Stretchable, Transparent Thin Film Transistors. (18th August 2016) - Tong, Kwing; Liang, Jiajie; Pei, Qibing
Abstract : Here, we report the development of a solution-processed thin-film field effect transistor (TFT) using silver nanowires as conductor, semiconductive single-walled carbon nanotubes as channel material, and polyurethane- co -polyethylene oxide as elastomeric dielectric. Intrinsically stretchable TFTs were fabricated in an elastomer matrix to exhibit deformability and preserve electrical conductivity at large strains. The silver nanowires were screen printed with conductivity as high as 4.67x10 4 S/cm. The TFTs exhibited a mobility of 30 cm 2 V -1 s -1, Ion/off of 10 3 -10 4, switching current >100 μA, transconductance >50 μS, and relatively low operating voltages. The devices retained a mobility >10 cm 2 V -1 s -1 at 50% strain and showed no significant loss after 500 cycles of stretching at 20% strain. Organic light-emitting diodes with brightness controllable from 0 cd/m 2 (off) to 200 cd/m 2 (typical display brightness) were driven by the stretchable TFTs. This approach represents an important progress toward the development of stretchable active matrix displays and other stretchable electronic devices.